Influence of Adiposity on the Gut Microbiota Composition of Arab Women: A Case-Control Study - Esra’a A. Aljazairy; Sara Al-Musharaf; Manal Abudawood; Basmah Almaarik; Syed D. Hussain; Abdullah M. Alnaami; Shaun Sabico; Nasser M. Al-Daghri; Mario Clerici; Ghadeer S. Aljuraiban (Biology, 2022)
Recent evidence has suggested that the gut microbiota is a possible risk factor for obesity. However, limited evidence is available on the association between the gut microbiota composition and obesity markers in the Middle-Eastern region. We aimed to investigate the association between gut microbiota and obesity markers in a case-control study including 92 Saudi women aged 18–25 years, including participants with obesity (case, n = 44) and with normal weight (control, n = 48). Anthropometric, body composition, and biochemical data were collected. The whole-genome shotgun technique was used to analyze the gut microbiota. The Shannon alpha and Bray–Curtis beta diversity were determined. The microbial alpha diversity was significantly associated with only the waist-to-hip ratio (WHR) (p-value = 0.04), while the microbial beta diversity was significantly associated with body mass index (p-value = 0.048), %body fat (p-value = 0.018), and WHR (p-value = 0.050). Specific bacteria at different taxonomic levels, such as Bacteroidetes and Synergistetes, were positively associated with different obesity markers. Alistipes was higher in the control group compared with the case group. The results highlight the association of the gut microbiota with obesity and suggest that the gut microbiota of Saudi women is associated with specific obesity markers. Future studies are needed to determine the role of the identified strains in the metabolism of individuals with obesity.